EFFECT OF MULAKABEEJADILEPA AND PRITHUNIMBAPANCHAKACHURNA IN VICHARCHIKA W.S.R. TO ECZEMA (AYUSHDHARA, 2018)
All Kustas are having Tridoshaja origin; hence Vicharchika can be explained in similar manner. Dermititis is being used as synonym of eczema by most of the dematologist. These are the kind of non-contagious inflammation of the skin characterized by erythema, Scaling, edema, vesiculation and oozing. The disease Vicharchika to a greater extent resembles eczema/dermatitis. Therefore the eczematous dermatitis can be included in study of Vicharchika. Vicharchika can be correlated with eczema in the sequence. The involvement of Vata results in dry, blackish lesion of eczema, itching in those affected areas is due to Kapha and Pitta is responsible for Srava. Though, the disease Vicharchika is not life threatening, it makes the patient worried due to its appearance, severe itching, disturbing routine and its nature susceptible to be chronic. In classical texts of Ayurveda Acharyas emphasizes Shodhana and Shamana therapy as the line of treatment at various contexts. Among the Shamana karma, Acharya chakradutta has advocated Lepana karma and Prithunimbapanchaka churna orally by (Sahasrayoga churna prakarana) for Vicharchika. Hence, purpose of the study aimed to evaluate efficacy of Mulakabeejadilepa and Prithunimba panchaka churna in Vicharchika. A case of 9yr old child, presented with Kandu, Pitika, Srava, Vivarnata, Vedana etc Lakshanas of Vicharchika on the back of his neck since one year, was given Mulakabeejadilepa as external application and Vati prepared with Prithunimbapanchaka churna 250mg TID for 30 days, and Marked improvement was observed in the symptoms of Vicharchika.